(untitled) (Texas Journal of Engineering and Technology, 2022)
The article discusses the inevitability of copper losses due to slag, as well as the possibility of decreasing them through various approaches and the use of local secondary technogenic formations. It has been demonstrated that the developed and commonly used in industry slag decontamination procedures only partially alleviate the problem and result in large irreversible metal losses with dump slag. The primary elements that influence the size of the losses are identified, and recommendations for limiting their negative impact are made. The use of ideal mixing equipment is advised in this scenario because a maximum decrease in the residual copper concentration in the waste slag is possible. With the organization and implementation of low-waste technologies, it is feasible to achieve an increase in the complexity of raw material utilization. In this article discusses about information of studying the possibilities of processing of mining slags.